(untitled) (Nepal Journal of Neuroscience, 2023)
Introduction: Chronic subdural hematoma (CSDH) is a common type of intracranial hemorrhage in elderly patients. The risk factors for recurrence of chronic subdural hematoma (CSDH) after surgical evacuation has not been completely understood until now, but several risk factors for recurrence have been reported. Meanwhile, the definitive risk factors have not been defined until now. The aim of this study was to study the potential risk factors, including preoperative, operative and post-operative ones for CSDH recurrence. Materials and Methods: The study population comprised of all > 18 year age group patients who were operated for chronic subdural hematoma in Neurosurgery Department of tertiary care center. It was prospective cohort study. Patients who met inclusion criteria, postoperative outcomes were assessed at discharge, then at one month and three months afterwards in the neurosurgery OPD. Both the treatment options i.e. BHC Burr hole craniotomy and minicraniotomy as required as per CT scan or MRI findings. Results: 7 patients (10.7%) had recurrence, of CSDH. All the reoccurrences occurred in burr hole operated patients. There was no recurrence in mini craniotomy operated group. Conclusions: Many risk factors for recurrence of CSDH have been found, including old age, cerebral atrophy, large hematoma, bilateral hematomas, hematoma density, inflammation markers, alcohol ingestion, bleeding tendency, and some technical aspects of surgery such as irrigation with small amount of fluid, not excising thick membrane preventing brain expansion.